Bridging the Generation Gap: Managing Conflict between Teachers and Students with the Wisdom of QS An-Nahl: 125 - Akbar Waliyuddin Pakpahan; Mahasri Shobahiya (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to explore the management of conflicts between teachers and students at SMK Sahid Surakarta by highlighting generational differences, expectations, values, and communication problems as the leading causes of conflict. This study integrates the wisdom principles of QS An-Nahl verse 125 and Carl Rogers' empathic approach to propose effective conflict resolution strategies. The strategy includes mediation, emotional education, counseling, and group discussions, expected to increase positive interactions between teachers and students. The method used in this study was qualitative, which included observation, interviews, and document analysis to understand the dynamics of conflict and improve the learning environment. The study results show that applying wisdom principles and restorative approaches can improve interpersonal relationships and create an inclusive school culture. This contributes to student well-being and more effective conflict resolution in the educational environment. This research is expected to provide insights for educators and school managers in creating a positive and supportive learning atmosphere and improving the overall quality of education.